Rereading the evidence of the earliest Christian communities in East Asia during and prior to the Táng Period - Morris, James Harry (Missiology, 2017)
The history of the church of the East in East Asia is one in which it is often difficult to divide fact and fiction. This is the result of an over-reliance on late 19th- and early 20th-century Orientalist scholarship, which sought to show the all-encompassing influence of Christianity in global history, and is often repeated in modern works without critical attention. In this article, I explore claims that Christianity arrived in Korea and Japan prior to the 9th century. I offer a critical assessment of these claims in order to suggest that they do not have an historical basis. Similarly, I seek to question what evidence we have to suggest that Christianity was present in pre-Táng dynasty China. I seek to illustrate that reliance on early scholarship has resulted in a number of fictional claims, which either cannot be maintained or require more research. The article seeks to act as a starting point for greater criticism of a number of assumptions made by scholars of early East Asian Christianity, historians and missiologists alike.